Study of biofilms by V. cholerae strains on the surfaces of biotic and abiotic substrates using mass spectrometry - M. V. Poleeva; O. S. Chemisova; E. A. Menshikova; M. M. Sagakyants; E. M. Kurbatova (Медицинский вестник Юга России, 2020)
Objective: identification and comparative study of protein spectra of Vibrio cholerae biofilms by MALDI-ToF mass spectrometry.Materials and methods: V. cholerae O1 strains isolated from different sources were studied. Methods: bacteriological, mass spectrometry.Results: mass spectrometric analysis showed that it was impossible to identify strains from “plankton” samples and from chitin and plastic plates. After culturing the biofilm and plankton strains, all of them were assigned to the V. cholerae species with a Score above 2,300. A сomparative analysis of MALDI-ToF mass spectra of different variants of V. cholera cultures revealed differences, while general peaks with different intensity were maintained.Conclusions: all samples of V. cholerae cultures taken for analysis aft er culture on a nutrient medium were reliably identified with a high Score. As a result of comparative analysis of protein mass spectra by the m/z value and relative intensity of peaks, no proteins characteristic only for plankton cultures or biofilms of V. cholerae were detected. The stability of the phenotypic properties of V. cholerae regardless of its form of existence and the high reliability of the MALDI-ToF mass spectrometry method for identifying both planktonic and biofilm forms of V. cholerae with the preservation of the research protocol and bacteriological culturation.